Exploring the community engagement experience of professors in a Nigerian University - Olutokunbo, Adekalu Samuel (2018)
In Nigeria, the government has invested in higher education with the intention of promoting human capacity development, particularly in public universities. So far, there has been no serious correction awareness aimed at addressing and promoting human resource development initiative through community engagement practices in Nigeria, especially in academic settings. Past research indicates that faculty members are not consistent in advancing the communities through exploration and mobilization of community resources, in facilitating and enhancing the skills, knowledge and attitude needed for learning, and career advancement, organizational development, and community development. This thesis examined the university community engagement among professors’ in Nigeria; inform by a qualitative case-study research approach. The study explored the career experiences of nine professors’ community engagement participation from nine academic departments in a Nigerian University. Qualitative methods were used; including in-depth, semi-structured interviewing interviews, direct observations, documentary analysis, literature review and consistent field notes. The study point to several potential strategies for making community engagement more sustainable, including incorporating community engagement into university policies, providing a more supportive institutional culture, facilitating engagement through reward and recognition of engaging academics, conducting continuous research into community problems, and encouraging engagement based on academics area of specialization. Also, the study provided empirical evidence of key factors that led to the professors’ community engagement participation at different stages in their career such as; organizational structure and incentives, upbringing and orientation, desire to change and impact people’s live, and personal satisfaction. More so, the study reveal the challenges and opportunities toward functional community engagement in academia. In addition, findings reveal the professors’ experience in regard to processes of their community engagement services in compliance with the institution philosophy as “the University for Community Development”. The understanding obtained regarding the career experience of professors’ community engagement in a Nigerian University envisages a number of recommendations to policy makers, practitioners, university management and faculty members to visualize sustaining community engagement and determined the needed interventions in implementing them. More importantly, this study revealed a number of theoretical and managerial implications for human resource development, in terms of knowledge generated on professors’ community engagement practices in Nigeria and the methodological insight used in deriving such knowledge, while suggesting directions for future research.